Alternatives to overcoming bacterial resistances: state-of-the-art - Rios, Alessandra C. (2016)
Abstract Worldwide, bacterial resistance to chemical antibiotics has reached such a high level that endangers public health. Presently, the adoption of alternative strategies that promote the elimination of resistant microbial strains from the environment is of utmost importance. This review discusses and analyses several (potential) alternative strategies to current chemical antibiotics. Bacteriophage (or phage) therapy, although not new, makes use of strictly lytic phage particles as an alternative, or a complement, in the antimicrobial treatment of bacterial infections. It is being rediscovered as a safe method, because these biological entities devoid of any metabolic machinery do not possess any affinity whatsoever to eukaryotic cells. Lysin therapy is also recognized as an innovative antimicrobial therapeutic option, since the topical administration of preparations containing purified recombinant lysins with amounts in the order of nanograms, in infections caused by Gram-positive bacteria, demonstrated a high therapeutic potential by causing immediate lysis of the target bacterial cells. Additionally, this therapy exhibits the potential to act synergistically when combined with certain chemical antibiotics already available on the market. Another potential alternative antimicrobial therapy is based on the use of antimicrobial peptides (AMPs), amphiphilic polypeptides that cause disruption of the bacterial membrane and can be used in the treatment of bacterial, fungal and viral infections, in the prevention of biofilm formation, and as antitumoral agents. Interestingly, bacteriocins are a common strategy of bacterial defense against other bacterial agents, eliminating the potential opponents of the former and increasing the number of available nutrients in the environment for their own growth. They can be applied in the food industry as biopreservatives and as probiotics, and also in fighting multi-resistant bacterial strains. The use of antibacterial antibodies promises to be extremely safe and effective. Additionally, vaccination emerges as one of the most promising preventive strategies. All these will be tackled in detail in this review paper.